Factors that influence employee retention in plant 3 at Guocera Sdn. Bhd. (Kluang Branch) / Ajlaa Nabihah Maslan - Maslan, Ajlaa Nabihah (Faculty of Business and Management, 2019)
Retaining an employee play a major important in an organization because a company will face tremendous lost when those employee resign as they are the assets of the company. However, the retention of employees has become the major problem facing today’s organizations The main purpose of conducting this research paper is analyze the factors that will influence employee retention in Plant 3 at Guocera Sdn Bhd (Kluang Branch). This study has been conducted at Plant 3 at Guocera Sdn Bhd (Kluang Branch) using questionnaires in order to collect the data from 86 respondents from non-executive at plant 3. This research paper contains four independent variables which compensation, training and development, work-life balance and workload. The data were collected using Statistical Package for Social Science (SPSS). The methods used in this research paper were Descriptive Analysis, Reliability Analysis, Pearson Correlation Analysis and Multiple Regression Analysis. The reliability of the scale was using Cronbach’s Alpha and was found higher than 0.6 and it consider reliable, good and valid for this research. For factor correlation analysis, all the variable have a strength and positive relationship (moderate & weak). Thus, all the result answered research question. In this research, only 30.5% of the employee retention explain by the variable, another 69.5% can be explain by the variable which are not included in this model. For the most significant relationship, the result show only compensation has a significant relationship with employee retention. While the other variable are not significant. Therefore, only 1 hypothesis is supported since there is significant effect between compensation and employee retention. The others hypothesis are rejected.